Teaching Shakespeare with purpose a student-centred approach - Thompson, Ayanna 1972-; Turchi, Laura (Arden Shakespeare, 2016)
"What does it mean to teach Shakespeare with purpose? It means freeing teachers from the notion that teaching Shakespeare means teaching everything, or teaching "Western Civilisation" and universal themes. Instead, this invigorating new book equips teachers to enable student-centred discovery of these complex texts. Because Shakespeare's plays are excellent vehicles for many topics-- history, socio-cultural norms and mores, vocabulary, rhetoric, literary tropes and terminology, performance history, performance strategie-- it is tempting to teach his plays as though they are good for teaching everything. This lens-free approach, however, often centres the classroom on the teacher as the expert and renders Shakespeare's plays as fixed, determined, and dead. Teaching Shakespeare with Purpose shows teachers how to approach Shakespeare's works as vehicles for collaborative exploration, to develop intentional frames for discovery, and to release the texts from over-determined interpretations. In other words, it presents how to teach Shakespeare's plays as living, breathing, and evolving dramas."--Back cover.